GENETIC PARAMETERS AND CHARACTERS ASSOCIATIONS IN TUBEROSUM POTATOES - Luthra, S K.; Gopal, J.; Pandey, S K.; Singh, B. P. (Potato Journal, 2013)
In Potato, tuber yield is a complex polygenic trait determined by interactions among genetical as well as environmental factors. The genetic variability along with heritability gives a reliable information of the genetic advance expected from population during selection for a character. Correlations among different characters are utilized in selection of better plant type and path coefficient analysis permits separation of correlation coefficients into components of direct and indirect effects. In the present investigation, 195 accessions of tuberosum group of potato were evaluated in RBD for five characters namely plant height (cm), stem number/plant, tuber yield/plant (g), tuber number/plant and average tuber weight (g) during three consecutive autumn crop seasons to estimate the genetic parameters and associations among characters for identification of promising parental lines. The analysis of variance revealed significant differences among the accessions for all the characters indicating prevalence of genetic variability. The high genotypic and phenotypic coefficients of variations, heritability and genetic advance were observed for tuber yield, tuber number and average tuber weight. Tuber yield possessed significantly positive correlation with all the characters. Plant height and stem number, however, had low direct effect on tuber yield and their positive contribution to tuber yield was mainly through average tuber weight and tuber number, respectively. Tuber number was negatively correlated with average tuber weight; therefore compromise between these two characters is necessary during selection for achieving high tuber yield. Forty eight accessions possessed significantly high tuber yield, 39 accessions, high tuber number and 38 accessions registered significantly high average tuber weight. Accessions CP1538 (476g/plant) and CP1515 (456g/plant) yielded higher than best control cv. Kufri Pukhraj (449g/plant) and possessed significantly higher tuber number (10) and average tuber weight (50g). Among top yielding accessions, CP1316 (541g/plant) possessed medium sized (34g) higher tuber numbers (16) and can be exploited for yield improvement as well as for production of varieties suitable for baby potatoes.